2023
DOI: 10.1590/1678-4685-gmb-2023-0126
|View full text |Cite|
|
Sign up to set email alerts
|

Neonatal screening for spinal muscular atrophy: A pilot study in Brazil

Alice Brinckmann Oliveira Netto,
Ana Carolina Brusius-Facchin,
Júlia F. Lemos
et al.

Abstract: Spinal muscular atrophy (SMA) is considered one of the most common autosomal recessive disorders, with an estimated incidence of 1 in 10,000 live births. Testing for SMA has been recommended for inclusion in neonatal screening (NBS) panels since there are several therapies available and there is evidence of greater efficacy when introduced in the pre/early symptomatic phases. In Brazil, the National Neonatal Screening Program tests for six diseases, with a new law issued in 2021 stating that it should incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 125 publications
0
8
0
Order By: Relevance
“…The review identified 37 cohort studies of newborn screening for SMA [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. No RCTs of newborn screening were identified.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The review identified 37 cohort studies of newborn screening for SMA [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. No RCTs of newborn screening were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Cohort studies relating to newborn screening programmes for SMA were identified from the following 17 countries ( Table 1 ): the UK [ 9 ], Belgium [ 10 , 11 , 12 ], Germany [ 13 , 14 , 15 , 16 , 17 , 18 ], Italy [ 19 , 20 ], Latvia [ 21 ], Portugal [ 22 ], Poland [ 23 ], Ukraine [ 24 ], Norway [ 25 ], Australia [ 26 , 27 , 28 , 29 ], the USA, Canada [ 30 , 31 , 32 ], Brazil [ 45 ], Japan [ 46 , 47 , 48 , 49 , 50 ], Taiwan [ 51 , 52 ], China [ 53 , 54 , 55 ] and Russia [ 56 , 57 ]. The USA screening programmes were reported for several US states: California [ 33 ], Georgia [ 34 ], Kentucky [ 35 ], Massachusetts [ 36 , 37 ], New York [ 38 , 39 , 40 ], North Carolina [ 41 ], Wisconsin [ 42 ], Utah [ 43 ] and Ohio [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations